Central European Infantry Handbooks in the Time of Early Modern Military Revolution - Andresová, Klára (Before the Battle, 2023)
The theory of early modern military revolution, which was presented by Michael Roberts in the 1950s and was later revised by various historians, is well known and still in use even today. One of the pillars of supposed revolution was a change of infantry training and a general change of infantry tactics, which first happened in the Netherlands in the 1590s. Another modification of infantry training and tactics took place in Sweden during the reign of Gustavus Adolphus. These transformations were reflected by a specific genre of period learned literature – military handbooks for infantry. Military manuals were published not only in Western Europe but also in Central Europe, mostly in Germany. In the period of 1550–1650, approximately 125 military handbooks were printed in ca. 225 editions. Twenty-five of these books were concerned specifically with the art of infantry war. Book history is a transdisciplinary field which offers new methods of studying military history. While researching changes of the content and formal aspects of military publications, we can trace changes of period military theory. The prosopography of military theorists and book publishers helps to reveal how the new ideas were disseminated – in this case how the new approaches to infantry training and the art of war spread from Western and Northern Europe to its centre. The aim of this contribution is not only to describe period infantry handbooks, but also to characterise the transfer of revolutionary changes in infantry warfare from Netherlands and Sweden into Central Europe with the help of period military manuals – especially those intended for infantry.